1991
DOI: 10.1128/iai.59.8.2529-2534.1991
|View full text |Cite
|
Sign up to set email alerts
|

Role of host cellular response in differential susceptibility of nonimmunized BALB/c mice to Plasmodium berghei and Plasmodium yoelii sporozoites

Abstract: We found BALB/c mice to be on the order of 2,000 times more susceptible to Plasmodium yoelii than Plasmodium berghei sporozoites, as measured by the ability of these sporozoites to differentiate into microscopically detectable hepatic schizonts in the livers of immunologically naive mice. One of the factors that determine the relative insusceptibility of mice to P. berghei sporozoites is the innate cellular inflammatory response that the mice mount after injection with sporozoites. The cellular inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
17
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 9 publications
(14 reference statements)
8
17
0
Order By: Relevance
“…These data suggest that P. yoelii sporozoites have a longer period of time during which they are infectious post-inoculation. While previous studies using intravenously inoculated sporozoites demonstrated that P. yoelii sporozoites develop better in the liver compared to P. berghei (16)(17)(18)(19), our results suggest that the higher infectivity of P. yoelii sporozoites is also due to their behavior in the skin, further supporting the notion that sporozoite motility in the dermis is a valid correlate for infectivity of the parasite. Recently a number of transgenic rodent parasite lines expressing P. falciparum or P. vivax CSP have been developed for pre-clinical vaccine testing in the rodent model (27)(28)(29).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These data suggest that P. yoelii sporozoites have a longer period of time during which they are infectious post-inoculation. While previous studies using intravenously inoculated sporozoites demonstrated that P. yoelii sporozoites develop better in the liver compared to P. berghei (16)(17)(18)(19), our results suggest that the higher infectivity of P. yoelii sporozoites is also due to their behavior in the skin, further supporting the notion that sporozoite motility in the dermis is a valid correlate for infectivity of the parasite. Recently a number of transgenic rodent parasite lines expressing P. falciparum or P. vivax CSP have been developed for pre-clinical vaccine testing in the rodent model (27)(28)(29).…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, while for both P. berghei and P. falciparum, these high-displacing sporozoites are no longer observed at 60 min after inoculation ( Figure 3D and 3F), P. yoelii sporozoites are still moving larger distances, with 3% of sporozoites moving between 50-200 μm in displacement at 60 and 120 min after inoculation ( Figure 3E). This difference in sporozoite behavior between the two rodent Plasmodium species is consistent with previous studies which showed that the infectivity of P. yoelii sporozoites to rodents is significantly higher than that of P. berghei sporozoites (16)(17)(18)(19) and is in line with the observation of a persistent exit of P. yoelii sporozoites out of the dermis into the circulation for over 2 hours after inoculation (10).…”
Section: Automated Sporozoite Detection and Trackingsupporting
confidence: 92%
See 1 more Smart Citation
“…In the following experiments we used the rodent parasite Plasmodium yoelii because infectivity of its sporozoites to laboratory rodents is significantly higher than that of P. berghei (Weiss, 1990;Khan and Vanderberg, 1991;Khusmith et al, 1991), thus allowing us to conduct meaningful quantitative studies of hepatic parasite loads. We first wished to establish the kinetics of sporozoite exit out of the inoculation site.…”
Section: Resultsmentioning
confidence: 99%
“…Data gathered from different mouse strains concerning the irradiated-attenuated sporozoite vaccine (4,15) were useful for designing vaccine trials in humans (2,3,(7)(8)(9)17). Previous studies have shown that BALB/c mice have a low susceptibility to P. berghei hepatic infection; only 0.01% of inoculated sporozoites infect the liver (13). This low susceptibility was correlated with the ability of BALB/c mice to elicit a cellular inflammatory response against the EE stages of P. berghei.…”
mentioning
confidence: 99%